Transport of Ebolavirus Nucleocapsids Is Dependent on Actin Polymerization: Live-Cell Imaging Analysis of Ebolavirus-Infected Cells - Schudt, Gordian; Dolnik, Olga; Kolesnikova, Larissa; Biedenkopf, Nadine; Herwig, Astrid; Becker, Stephan (The Journal of infectious diseases, 2015)
Transport of ebolavirus (EBOV) nucleocapsids from perinuclear viral inclusions, where they are formed, to the site of budding at the plasma membrane represents an obligatory step of virus assembly. Until now, no live-cell studies on EBOV nucleocapsid transport have been performed, and participation of host cellular factors in this process, as well as the trajectories and speed of nucleocapsid transport, remain unknown. Live-cell imaging of EBOV-infected cells treated with different inhibitors of cellular cytoskeleton was used for the identification of cellular proteins involved in the nucleocapsid transport. EBOV nucleocapsids were visualized by expression of green fluorescent protein (GFP)-labeled nucleocapsid viral protein 30 (VP30) in EBOV-infected cells. Incorporation of the fusion protein VP30-GFP into EBOV nucleocapsids was confirmed by Western blot and indirect immunofluorescence analyses. Importantly, VP30-GFP fluorescence was readily detectable in the densely packed nucleocapsids inside perinuclear viral inclusions and in the dispersed rod-like nucleocapsids located outside of viral inclusions. Live-cell imaging of EBOV-infected cells revealed exit of single nucleocapsids from the viral inclusions and their intricate transport within the cytoplasm before budding at the plasma membrane. Nucleocapsid transport was arrested upon depolymerization of actin filaments (F-actin) and inhibition of the actin-nucleating Arp2/3 complex, and it was not altered upon depolymerization of microtubules or inhibition of N-WASP. Actin comet tails were often detected at the rear end of nucleocapsids. Marginally located nucleocapsids entered filopodia, moved inside, and budded from the tip of these thin cellular protrusions. Live-cell imaging of EBOV-infected cells revealed actin-dependent long-distance transport of EBOV nucleocapsids before budding at the cell surface. These findings provide useful insights into EBOV assembly and have potential application in the development of antivirals.